2009
DOI: 10.1094/mpmi-22-4-0411
|View full text |Cite
|
Sign up to set email alerts
|

The Magnaporthe oryzae Avirulence Gene AvrPiz-t Encodes a Predicted Secreted Protein That Triggers the Immunity in Rice Mediated by the Blast Resistance Gene Piz-t

Abstract: The Magnaporthe oryzae avirulence gene AvrPiz-t activates immunity in a gene-for-gene fashion to rice mediated by the blast resistance gene Piz-t. To dissect the molecular mechanism underlying their recognition, we initiated the cloning of AvrPiz-t using a map-based cloning strategy. The AvrPiz-t gene was delimited to an approximately 21-kb genomic fragment, in which six genes were predicted. Complementation tests of each of these six candidate genes led to the final identification of AvrPiz-t, which encodes a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
202
0
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 244 publications
(217 citation statements)
references
References 59 publications
2
202
0
3
Order By: Relevance
“…In addition to Slp1, more than a dozen effector proteins have been identified in M. oryzae, such as Pwl2 (for pathogenicity toward weeping lovegrass protein2) (Sweigard et al, 1995), AVR-Pita1 (Jia et al, 2000), AVR-Pia (Miki et al, 2009;Yoshida et al, 2009), AVR-Pik/km/kp, AVR-Pii (Yoshida et al, 2009), AVR-CO39 (Farman et al, 2002), Bas1 to Bas4 (Mosquera et al, 2009), and AvrPiz-t (Li et al, 2009). N-Glycosylation sites are predicted in some of these effector proteins, including Bas2, Bas4, and AvrPiz-t, suggesting that Alg3 may mediate the N-glycosylation of several effector proteins in M. oryzae during plant infection.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to Slp1, more than a dozen effector proteins have been identified in M. oryzae, such as Pwl2 (for pathogenicity toward weeping lovegrass protein2) (Sweigard et al, 1995), AVR-Pita1 (Jia et al, 2000), AVR-Pia (Miki et al, 2009;Yoshida et al, 2009), AVR-Pik/km/kp, AVR-Pii (Yoshida et al, 2009), AVR-CO39 (Farman et al, 2002), Bas1 to Bas4 (Mosquera et al, 2009), and AvrPiz-t (Li et al, 2009). N-Glycosylation sites are predicted in some of these effector proteins, including Bas2, Bas4, and AvrPiz-t, suggesting that Alg3 may mediate the N-glycosylation of several effector proteins in M. oryzae during plant infection.…”
Section: Discussionmentioning
confidence: 99%
“…AVR-Pita1 (Orbach et al, 2000;Khang et al, 2008), which confers AVR toward rice containing the corresponding R gene Pita , encodes a putative zinc metalloprotease. Additional cloned AVR genes are AVR1-CO39 and AvrPiz-t, which were identified by map-based cloning (Farman and Leong, 1998;Li et al, 2009), AVR-Pii and AVR-Pik/km/kp, which were identified by fungal genome resequencing and association genetics (Yoshida et al, 2009), and AVR-Pia, which was cloned independently using association genetics and spontaneous mutant analysis (Shinsuke et al, 2009;Yoshida et al, 2009). Transient expression of AVR-Pita1, AVR-Pia, AVR-Pii, and AVR-Pik/km/kp proteins in rice with the cognate R gene product suggested that they function after secretion from the fungus and translocation into the rice cytoplasm Yoshida et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Rice blast fungus is a representative model phytopathogenic fungus for which gene-for-gene interactions with the host are applicable. To date, more than 40 resistance genes have been identified in host rice and among the corresponding pathogen avirulence, 9 genes have been identified through molecular biology and functional genetics [37][38][39][40][41][42]. As a strategy to control rice blast fungus, introduction of a resistance gene through breeding is considered to be most effective.…”
Section: Resultsmentioning
confidence: 99%